Subacute sclerosing panencephalitis presenting as neuromyelitis optica - Raut, Tushar Premraj (BMJ Case Rep, 2012)
Subacute sclerosing panencephalitis (SSPE) is a slowly progressing inflammatory and degenerative disorder of the brain caused by a mutant measles virus. The diagnosis of SSPE is based on characteristic clinical and EEG findings (periodic complexes) and demonstration of elevated antibody titres against measles in cerebrospinal fluid. SSPE can have atypical clinical features at the onset. The authors here report a case of a 3-year-old child who presented with vision loss followed 15 months later by quadriparesis with bladder involvement. These clinical features resembled that of neuromyelitis optica. However, as the disease progressed, appearance of myoclonic jerks, periodic discharges on EEG and positive cerebrospinal fluid serology for measles led to the final diagnosis of SSPE.